2018
DOI: 10.1002/clc.22981
|View full text |Cite
|
Sign up to set email alerts
|

Rate pressure product and the components of heart rate and systolic blood pressure in hospitalized heart failure patients with preserved ejection fraction: Insights from ASCEND‐HF

Abstract: Background Heart rate and systolic blood pressure (SBP) are prognostic markers in heart failure (HF) with reduced ejection fraction (HFrEF). Their combination in rate pressure product (RPP) as well as their role in heart failure with preserved ejection fraction (HFpEF) remains unclear. Hypothesis RPP and its components are associated with HFpEF outcomes. Methods We performed an analysis of Acute Study of Clinical Effectiveness of Nesiritide in Subjects With Decompensated Heart Failure (ASCEND‐HF; http://www.cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
2
16
1
Order By: Relevance
“…In the Acute Study of Clinical Effectiveness of Nesiritide in Subjects With Decompensated Heart Failure (ASCEND‐HF), an in‐hospital rise of DP from baseline to discharge but not DP at baseline alone was associated with higher 30‐day mortality/HF hospitalization in patients with HFpEF 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Acute Study of Clinical Effectiveness of Nesiritide in Subjects With Decompensated Heart Failure (ASCEND‐HF), an in‐hospital rise of DP from baseline to discharge but not DP at baseline alone was associated with higher 30‐day mortality/HF hospitalization in patients with HFpEF 12 …”
Section: Introductionmentioning
confidence: 99%
“…11 In the Acute Study of Clinical Effectiveness of Nesiritide in Subjects With Decompensated Heart Failure (ASCEND-HF), an in-hospital rise of DP from baseline to discharge but not DP at baseline alone was associated with higher 30-day mortality/HF hospitalization in patients with HFpEF. 12 The aim of our study was to analyze the role of blood pressure components SBP, DBP, and PP as well as the double product on CV mortality and all-cause mortality in a patient cohort with a high percentage of coronary artery disease (CAD) and heart failure (HF).…”
mentioning
confidence: 99%
“…This study was the rst to provide the concept of SBP × HR / LVEF representing CLI. The SBP and HR product is an indirect index of cardiac work, which can predict cardiac function, morbidity, and mortality in patients with cardiovascular disease [10]. LVEF is a valuable diagnostic and prognostic tool for cardiovascular disease, and re ects cardiac function and remodeling [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the RPP highly correlates with invasive measurement of myocardial oxygen consumption, and it is used as an index of myocardial workload and oxygen demand to predict cardiac function, morbidity and mortality 11,12 . Cardiovascular reactivity to acute stress is mediated via the activation of the sympathetic nervous system and hypothalamus-pituitary-adrenal axis, leading to increase in heart rate, blood pressure, vasoconstriction, and vagal withdrawal 13 .…”
Section: Discussionmentioning
confidence: 99%